METODE FIVE PLANES DAN SUS PADA DESAIN UI/UX SISTEM RESERVASI - Sekar Ayu Nabila; Kusnadi Kusnadi; Viar Dwi Kartika (LPPM Politeknik Pratama Kendal, 2026)
This research focuses on crafting a seamless and intuitive user interface and experience through a reservation website tailored for Terajeh Coffee & Steak House, located in Cirebon City. The main issue addressed is the limitation of social media in providing comprehensive information about menus, reservations, and brand identity, thus necessitating a more representative website to support the digital transformation of this F&B business. The research employs the Five Planes approach, consisting of five strategic stages from identifying objectives and user needs to the visual interface. Figma was used to develop wireframes and prototypes, while Maze facilitated user interaction testing. The usability assessment was conducted using the System Usability Scale (SUS) method, where users filled out a questionnaire after directly interacting with the developed prototype. The results show an informative and interactive website prototype with an SUS score falling into the good category, although there are still suggestions for improving navigation and visual elements. This study is important as it offers a systematic approach to UI/UX design that can enhance user experience and strengthen business image, although it does not yet cover the full functional development of the website.